Over-the-Scope Clip Closure of Persistent Gastrocutaneous Fistula After Percutaneous Endoscopic Gastrostomy Tube Removal: A Report of Two Cases - Masaki, Shigenori (Cureus, 2021)
Persistent gastrocutaneous fistulas have conventionally been treated surgically. Over-the-scope clip (OTSC) was developed as an endoscopic closure device for full-thickness gastrointestinal defects and has become one of the treatment options for gastrocutaneous fistula. Herein, we report two cases of gastrocutaneous fistulas treated using OTSC. Case 1 was a 71-year-old woman and case 2 was an 88-year-old man, both of whom had severe frailty and had a persistent gastrocutaneous fistula after removal of the percutaneous endoscopic gastrostomy (PEG) tube. OTSC closure was chosen over surgical closure to reduce invasiveness. In case 1, OTSC was deployed using a suction method, which was technically successful. However, the fistula reopened two days later, indicating clinical failure of the OTSC. The cause of the failure may be due to an inadequate suction of the fistula into the applicator cap. Based on the experience of OTSC failure in case 1, OTSC in case 2 was deployed using the Anchor to pull the fistula into the cap more reliably. Fistula did not recur during the 30-month follow-up, indicating the clinical success of OTSC in case 2. The use of Anchor may increase the success rate of OTSC, but there is a dilemma that the use of Anchor increases cost. In summary, OTSC has the advantage of being less invasive compared to conventional surgery; however, the application of OTSC for chronic fistulas remains challenging due to issues regarding clinical success rate and cost.